1995
DOI: 10.1002/jctb.280620106
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol production by alginate immobilised yeast in a fluidised bed bioreactor

Abstract: Yeast, immobilised in alginate beads of known standard size and mechanical strength, has been utilised in a novel design of fluidised bed bioreactor which avoids problems of particle flotation and gas logging. Circulating substrate simultaneously entered the top and bottom of the bed. The bioreactor operated reliably for periods of up to 20 days. Increasing alginate concentration in the range 1–5% (w/w) had little effect on the performance of the immobilised yeast in converting ethanol to glucose but reduced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 15 publications
1
14
0
1
Order By: Relevance
“…Among them all, alginate is certainly the most widely used material. The most promising applications of alginate gels are in the field of cell microencapsulation (Donati and Paoletti, 2009), as in (micro) bio-reactors for the production of chemicals (Gilson and Thomas, 1995) and high-added value bio-chemicals, or as encapsulation matrices in tissue engineering, with adult (Kinasiewicz et al, 2008;Siebers et al, 1997) and stem cells (Maguire et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among them all, alginate is certainly the most widely used material. The most promising applications of alginate gels are in the field of cell microencapsulation (Donati and Paoletti, 2009), as in (micro) bio-reactors for the production of chemicals (Gilson and Thomas, 1995) and high-added value bio-chemicals, or as encapsulation matrices in tissue engineering, with adult (Kinasiewicz et al, 2008;Siebers et al, 1997) and stem cells (Maguire et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, 30% of the industries have substituted batch by continuous fermentation processes (Wheals et al, 1999) because this presented several advantages. To improve the productivity and ethanol yield and to avoid the utilization of centrifuges that are expensive, continuous processes with immobilized cells in different carriers as glass, synthetic polymers as polyacrylamide (Lida, 1993) and polypropilene gels (Inloes et al, 1983), calcium alginate (Bravo and Gonzales, 1991;Gilson and Thomas, 1995;Roukas, 1994;Sanches et al, 1996), kissiris (Argiriou et al, 1996) have been suggested, although some carriers presented difficulties at industrial scale. For example, alginate beads that can be destroyed due to friction and CO 2 evolution inside the beads (Gilson and Thomas, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…(Sitton and Gaddy (1980)). Conversions in fluidized bed reactors were better than batch reactor (Gilson and Thomas (1995) (Najafpour, et al (2004)). Figure 7,8 show the similar behavior of 4% sodium alginate made beads shown better performance than 2% and 6% sodium alginate beads for packed and fluidized bed bio-reactors.…”
Section: Resultsmentioning
confidence: 99%